Functionally graded NiTi alloy with exceptional strain-hardening effect fabricated by SLM method. (November 2020) - Yang, Y.; Zhan, J.B.; Sui, J.B.; Li, C.Q.; Yang, K.; Castany, P.; Gloriant, T.
Abstract: In this study, we have employed a repetitive laser scanning strategy to fabricate a three-dimensional functionally graded NiTi alloy by SLM method. The microstructure shows gradient characterized by the increase of volume fraction for B19' phase. An exceptional strain-hardening associated with continuous increase of mechanical recoverable strain is obtained in such material. The gradient of functionality is attributed to the superimposition of multi-deformation mechanisms originating from the microstructural gradient. The deformation mechanisms are dominated by reorientation of B19' variants at early stage of deformation and then by stress-induced martensitic transformation at higher level of stress. Graphical abstract: Image, graphical abstract